2022
DOI: 10.3389/fonc.2022.934735
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning-based contrast-enhanced computed tomography radiomic analysis for categorization of ovarian tumors

Abstract: ObjectivesThis study aims to evaluate the diagnostic performance of machine-learning-based contrast-enhanced CT radiomic analysis for categorizing benign and malignant ovarian tumors.MethodsA total of 1,329 patients with ovarian tumors were randomly divided into a training cohort (N=930) and a validation cohort (N=399). All tumors were resected, and pathological findings were confirmed. Radiomic features were extracted from the portal venous phase images of contrast-enhanced CT. The clinical predictors include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Additionally, one paper (1.8%) described both differential diagnosis and prognostic prediction. We found that assessments of differential diagnosis and prognostic prediction were both commonly performed; thus, 16 articles focusing on the differential diagnosis of OC [ 24 26 , 28 - 32 , 34 , 35 , 39 , 40 , 42 , 44 , 45 , 47 ] and 13 that described studies on prognostic factors [ 52 , 53 , 55 57 , 64 , 66 68 , 71 74 ] were subjected to separate meta-analyses.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, one paper (1.8%) described both differential diagnosis and prognostic prediction. We found that assessments of differential diagnosis and prognostic prediction were both commonly performed; thus, 16 articles focusing on the differential diagnosis of OC [ 24 26 , 28 - 32 , 34 , 35 , 39 , 40 , 42 , 44 , 45 , 47 ] and 13 that described studies on prognostic factors [ 52 , 53 , 55 57 , 64 , 66 68 , 71 74 ] were subjected to separate meta-analyses.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Using non-contrast CT images, Li et al [149] constructed and externally validated a radiomics model and nomogram with good-to-excellent performance (AUC of 0.83 and 0.95, respectively) for the differential diagnosis between benign and malignant ovarian tumours. A large study including 1329 patients with ovarian tumours provided an AUC of 0.91 of the machine-learning-based radiomics model for the differentiation between the benign and malignant tumours on contrast-enhanced CT [150]. Furthermore, a multicentric study involving 665 patients from four centres reported an AUC of 0.836 for differentiating high-grade and non-high-grade serous carcinoma [151].…”
Section: Ctmentioning
confidence: 99%